Do we need national champions?: if so, do we need a champions-related industrial policy? ; an evolutionary perspective - Oliver Falck; Stephan Heblich (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
This paper discusses the role of so-called national champions within the context of the EUs ambitious goal to become the most competitive and dynamic knowledge-based economic region in the world by 2010. We find football to be a useful analogy in our discussion of national champions. There are many different types of football players: veteran performers who are past their prime, young stars who have not yet developed their full potential, fans darlings, and the actual starsthe key performers. For a team to be consistently successful across time, it needs to maintain the right mix of different types of players, particularly in regard to current and future key performers. What makes a key performer a real star is not only extraordinary talent but also, and perhaps even more important, ability to be a team player and inspire others to be the same. Applying this analogy to the economic field, we come to the conclusion that the real champions in the business environment serve as network pilots within regional networks. By fostering a dynamic economic environment, they create their own rents, unlike less successful firms who concentrate on unproductive rent seeking and shifting.
Keywords: L52; O25; O33; P11; 330; national champions; industrial policy; evolutionary economics; systems of innovation; Industriepolitik; Innovationspolitik; Business Network; Regionale Konzentration; Evolutionsökonomik; Deutschland